Neoadjuvant chemotherapy in advanced gastric and esophago-gastric cancer. Meta-analysis of randomized trials. (March 2018) - Coccolini, Federico; Nardi, Matteo; Montori, Giulia; Ceresoli, Marco; Celotti, Andrea; Cascinu, Stefano; Fugazzola, Paola; Tomasoni, Matteo; Glehen, Olivier; Catena, Fausto; Yonemura, Yutaka; Ansaloni, Luca
Abstract: Introduction: Even in after curative surgery and adequate linfoadenectomy the survival of advanced gastric cancer (AGC) remains poor. At present some data have been published on the effects of NACT and perioperative chemotherapy on AGC and Esophago-gastric cancer (EGC) but not definitive ones. The present meta-analysis aims to evaluate the effects of neoadjuvant chemotherapy (NACT) on the AGC and EGC. Material and methods: A systematic review with meta-analysis of randomized controlled trials (RCTs) of NACT + surgery vs. Surgery in patients with AGC and EGC was performed. Results: 15 RCTs have been included (2001 patients: 977 into NACT + surgery arm and 1024 into control arm). NACT + Surgery reduces the overall mortality at 1, 3 and 5-year in cumulative analysis (RR = 0.78; 0.81; 0.88 respectively), at 1, 2, 3 and 5-years in EGC (RR = 0.79; 0.83; 0.84; 0.91 respectively) and at 3 and 5-years in AGC (RR = 0.74; 0.82 respectively). Morbidity and perioperative mortality rate are not influenced by NACT. Recurrence rate is reduced by NACT + surgery in EGC (RR = 0.80). Conclusions: NACT reduces the mortality in gastric and esophago-gastric cancer. Morbidity and perioperative mortality are not influenced by NACT. The overall recurrence rate is reduced by NACT in esophago-gastric cancer. Highlights: Neoadjuvant chemotherapy in gastric and esophago-gastric cancer. Neoadjuvant chemotherapy reduces the overall mortality in gastric and esophago-gastric cancer. Neoadjuvant chemotherapy doesn't increase the morbidity rate.